Tofacitinib: an Option for Acute Severe Ulcerative Colitis? - Santos, S (2022)
Tofacitinib has emerged as a new option for ulcerative colitis. Its rapid absorption, metabolism, and clinical improvement make it an interesting option for rescue therapy in acute severe ulcerative colitis (ASUC), a situation with limited therapeutic options in patients with a long-term disease course and multiple drug failure. The management of ASUC in this setting becomes challenging, underlying the need for new drugs and data on their efficacy and safety. We describe 2 cases of acute episodes in which tofacitinib was used as a rescue therapy.